Molecular Pathology of Liver Diseases - Monga, Satdarshan P. S. (Molecular Pathology Library, 2011)
Molecular Pathology of Liver Diseases integrates the traditional knowledge of physiological and pathological processes in the liver with a balanced emphasis on fundamental concepts; timely advances in cellular and molecular mechanisms; and applied pathology. The textbook is organized into several sections, each of which includes an array of chapters that progressively and cohesively elaborate on pertinent liver biology and pathology. The first three sections discuss the cellular composition of the liver along with their specialized functions, and further dissect the molecular basis of the cellular processes that are so unique to the liver. The next section examines the mechanisms that are commonly implicated in the cellular and molecular basis of several hepatic pathologies, followed eventually by a section each on a multitude of non-neoplastic and neoplastic diseases of the liver. Molecular Pathology of Liver Diseases is a comprehensive reference on liver pathobiology for basic, translational and clinical researchers and physicians The format of the volume will serve as a ready reference to relevant topics in the liver, thus providing a practical disease-based integrative resource on the molecular pathology of liver disease. Satdarshan (Paul) Singh Monga, MD is Director: Division of Experimental Pathology and Associate Professor of Pathology and Medicine, University of Pittsburgh, Pittsburgh, PA.